2018
DOI: 10.3390/polym10111208
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Processing Parameters on Tensile Properties of SLS Polymer Product

Abstract: Polymer products manufactured by additive processes are today increasingly flooding the market. Given that they have broad application ranging from various consumer products to medicine and automotive industry, the products must satisfy certain mechanical properties. In the past studies of selective laser sintering (SLS) for polymer materials, the processing parameter of energy density has been confirmed which affects the tensile properties. Energy density depends on the laser beam speed, laser power and hatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 23 publications
3
46
0
Order By: Relevance
“…Pilipović et al [8] and Wegner and Witt [4] showed that the layer thickness has a very large influence on the part properties. An increase of layer thickness resulted in a decrease of the part density and the tensile properties and therefore recommend to strive for a layer thickness as thin as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Pilipović et al [8] and Wegner and Witt [4] showed that the layer thickness has a very large influence on the part properties. An increase of layer thickness resulted in a decrease of the part density and the tensile properties and therefore recommend to strive for a layer thickness as thin as possible.…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the influence of these three factors on powder forming, an orthogonal experiment of three factors and three levels was designed. According to [19], the reasonable scanning speed ranges from 2700 mm s −1 to 3300 mm s −1 . The reasonable variation range of the laser scanning power can be then roughly estimated.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have focused their work on the geometrical accuracy of samples obtained at different orientations and/or energy density by measuring the size and shape and inspecting the surface of the parts by stereomicroscopy [11][12][13] without taking into account the mechanical aspects that are directly influenced by the process parameters. The mechanical characterization of SLS polymer parts was conducted through tensile tests by some authors [14], while in other studies flexural properties were determined according to the manufacturing parameters [15,16]. However, the process parameters greatly influence the mechanical properties of the samples.…”
Section: Introductionmentioning
confidence: 99%